Strata as a Fangirl: How K-Pop Influencers Create a New Culture in Fangirling - Pramesthi, Jasmine Alya (Mahesa Research Center, 2025)
This article addresses the limited research connecting fangirling with power relations in digital fandom and aims to analyze the role of K-Pop influencers in shaping collective opinion. The study focuses on how audiences, as active fans, perceive the symbolic influence of these figures. Employing a qualitative case study approach, the research involved participatory observation on Twitter, TikTok, and Instagram, in-depth interviews with eight informants, and an exploratory survey of 20 K-Pop fans. Data were analyzed using thematic analysis with Gramscian hegemony as the analytical lens. The findings indicate that most audiences (75%) tend to follow influencers’ directions without questioning, reflecting hegemonic practices sustained by affection, loyalty, and cultural consent. On the other hand, resistance also emerged, with some fans perceiving influencer dominance as limiting the space for open discussion. The study concludes that fangirling is a paradoxical cultural practice: while it fosters collective solidarity, it may also generate exclusivity and conflict. This research contributes novelty by framing hegemony as a fluid and negotiated practice, embedded in affective relations and digital interactions within fandom communities.